Coaches representation about detection and selection of talents on the Brazilian volleyball - Milistetd, M.; Mesquita, I.; Sobrinho, S. A.; Carrara, P.; Nascimento, J. (International Journal of Sports Science, 2013)
The aim of this study was to analyse the representations of coaches about detection and selection of talent in Brazilian volleyball. Ten volleyball coaches working with junior categories were interviewed. A semi-structured interview was used and the comments were subsequently examined by content analysis. The encoding table used was based on Fernandes (2004). Concerning talent detection, coaches indicated as essential youth biotype, with height as the key indicator. In addition, they considered very important the technical resource and it is essential to enjoy the practice. For the young talent selection, it is important to evaluate the different components of training - technical and physical indicators. With regard to ways of talent detection, coaches cited the scholar competitions as a context for evaluation, but subjectively. In the young talent methods of selection, the process must be developed in a long term, when the more skilled develop their ability to optimize performance. It was observed that coaches employ empiric beliefs, maybe due to a lack of systematic education for volleyball coaches in Brazil.